Kualitas pelayanan IGD sebagai kunci utama untuk meningkatkan kepuasan dan loyalitas pasien di Rumah Sakit Umum Daerah Karanganyar - Nurjanah, Adha; Sutrisna, Em; Isa, Muzakar (Nur Science Institute, 2025)
This study aims to analyze the effect of service quality on patient satisfaction and loyalty, as well as the impact of the length of waiting time for patient transfer from the ER to the inpatient room on the quality of ER services at Karanganyar District Hospital. This research approach employs a mixed-methods approach, combining qualitative and quantitative aspects. From the qualitative side, data collection was carried out on informants in charge of the ER, and from the quantitative side, data collection was carried out using a purposive sampling technique that collected 93 patient respondents. The findings show that service quality and patient satisfaction have a significant positive effect on loyalty, and service quality also has a significant positive effect on patient satisfaction. The causes of the long transfer of ER patients to the inpatient room at Karanganyar District Hospital include DPJP doctors who are difficult to contact, DPJP doctors who have special requests for patient care in the ER, Bed management systems that have not been running, full inpatient rooms, laboratory results that take a long time for specific examinations, radiology reading results that take a long time because radiology specialist doctors are not on standby on day and night shifts, patient escorts or porters who are challenging to find.